تصورات الطالبة الجامعية حول إستخدام مستحضرات التجميل في ضوء الضغط النفسي الناجم عن إستخدامها - قاسمية، إيمان, بن ياية، فردوس (جامعة الوادي university of Eloued, 2017)
الملخص: تهدف الدراسة إلى الكشف عن تصورات الطالبة الجامعية حولاستخدام مستحضرات التجميل في ضوء الضغط النفسي الناجم عن استخدامها، ولمعرفة ذلك قمنا بإستخدام المنهج الوصفي الإستكشافي وذلك لملائمتها موضوع دراستنا وعلى ضوء دراستنا وعلى ضوء اهداف البحث تساؤلات الدراسة تمت تطبيقيا أداة قياس المتمثلة في الإستبيان على عينة قصدية صدفية لطالبات جامعة الشهيد حمة لخضر بالوادي والتي تكونت من (63) طالبة موزعة عبر مختلف الكليات، حيث كان الإشكال العام لدراستنا: ماهي تصورات الطالبة الجامعية حول استخدام مستحضرات التجميل في ضوء الضغط النفسي الناجم عناستخدامها؟ واندرجت تحته تساؤلات فرعية والتي كانت على النحو التالي: هل يوجد اختلاف في استجابة الطالبات تبعا لمصادر ضغوط استخدام مستحضرات التجميل تعزى لمتغير المستوى الدراسي(ليسانس، ماستر)؟ هل يوجد اختلاف في استجابة الطالبات تبعا لمصادر الضغط؟ وقد أظهرت نتائج الدراسة على وجود اختلاف في تصورات الطالبة الجامعية حول استخدام مستحضرات التجميل في ضوء الضغط النفسي الناجم عن استخدامها وبالتالي الطالبة لديها تصورات إيجابية حول استخدامه، كما لا يوجد اختلاف في استجابة الطالبات تبعا لمصادر ضغوط استخدام مستحضرات التجميل تعزى لمتغير المستوى الدراسي (ليسانس، ماستر)، ويوجد اختلاف أيضا في استجابة الطالبات تبعا لصادر الضغط، كما قمنا في الأخير بطرح اقتراحات وآفاق للدراسة من شأنها أن تثري الرصيد المعرفي للباحث أو المطلع عليها. Study summary in English: The study aims to reveal the perceptions of the university student about the use of cosmetics in the light of the psychological stress resulting from their use. we used the descriptive approach for its relevance to the subject of our study.in the light of the research objectives and questions of the study, a measurement tool was used of questionnaire on a random sampling of the students of the University Hama Lakhdar in Eloued, Which consisted of (63) students distributed across different faculties, whereas the general problem of our study is: What are the perceptions of the university student about the use of cosmetics in the light of the psychological stress resulting from their use? Below it were sub-questions which were as follows: Is there a difference in the response of students according to the sources of stress on the use of cosmetics due level of study (bachelor, master)? Is there a difference in the response of students according to sources of stress? The results of the study showed that there is a difference in the perceptions of the university student about the use of cosmetics in light of the psychological stress resulting from the use, Thus the student has positive perceptions about its use.There is also no difference in the response of students according to sources of stress used cosmetics due to the variable level of study (License, Master), There is also a difference in the response of students according to the source of stress. We also put forward proposals and prospects for the study that will enrich the knowledge of the researcher or the familiar.
دراسة ميدانية لطالبات جامعة الشهيد حمة لخضر الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: التصورات الجامعية، مستحضرات التجميل، الضغوط النفسية; Perceptions universitaires, cosmétiques, stress psychologique; University perceptions, cosmetics, psychological stress